Development of small-molecule sting activators for cancer immunotherapy - Jung, Hee Ra; Jo, Seongman; Jeon, Min Jae; Lee, Hyelim; Chu, Yeonjeong; Lee, Jeehee; Kim, Eunha; Song, Gyu Yong; Jung, Cheulhee; Kim, Hyejin; Lee, Sanghee (Biomedicines, 2022)
In cancer immunotherapy, the cyclic GMP–AMP synthase–stimulator of interferon genes (STING) pathway is an attractive target for switching the tumor immunophenotype from ‘cold’ to ‘hot’ through the activation of the type I interferon response. To develop a new chemical entity for STING activator to improve cyclic GMP-AMP (cGAMP)-induced innate immune response, we identified KAS-08 via the structural modification of DW2282, which was previously reported as an anti-cancer agent with an unknown mechanism. Further investigation revealed that direct STING binding or the enhanced phosphorylation of STING and downstream effectors were responsible for DW2282-or KAS-08-mediated STING activity. Furthermore, KAS-08 was validated as an effective STING pathway activator in vitro and in vivo. The synergistic effect of cGAMP-mediated immunity and efficient anti-cancer effects successfully demonstrated the therapeutic potential of KAS-08 for combination therapy in cancer treatment.
Keywords: Cancer immunotherapy; STING; STING activator; Type I interferon